Model of Economic Development on the Way to Overcome Unemployment and Labor Force Growth - MAXIMILIAN, Silvestru; GRIBINCEA, Alexandru A.; GRIBINCEA, Corina; HABASHI, Manal; SANDU, Maxim (Journal of Advanced Research in Law and Economics, 2019)
In the modern world, in the context of the global economic crisis, the problem of employment is urgent. The main feature of staff in an enterprise is the degree of individual responsibility for the ultimate outcome of organization and creativity at each workplace within the organization. Attitudes towards staff have come from treating them as a work force, like a traction animal, to treating staff as human capital: the attitude towards them has changed, the employees' responsibility for the result. Therefore, the main objective of the work is to develop a model of economic growth. Determined that an important indicator of labor resources is its quantity. The number of labor resources is influenced by demographic factors: fertility and mortality. The peculiarity of the labor market is related to the specific nature of the product itself – the inseparability of the owner of the workforce; the buyer only receives the right to use part of the workforce for a certain period of time; legal liability is possible; economic damage due to loss of loyalty, because the employee can work with different returns.